Brivaracetam use in children with epilepsy: A retrospective multicenter study - Špilárová, Z; Sládková, S; Bělohlávková, A; Česká, K; Hanáková, P; Horák, O; Jahodová, A; Knedlíková, L; Kolář, S; Ebel, M; Kudr, M; Ošlejšková, H; et al. (Seizure, 2024)
PURPOSE: This retrospective multicenter study aimed to assess the efficacy and safety of brivaracetam (BRV) in pediatric epilepsy. METHODS: Our cohort consisted of 93 children (mean age 11.5 ± 7.5 years) with a wide spectrum of pediatric epilepsy, including epileptic encephalopathy and generalized epilepsy. Of these, 61 (60.4%) were diagnosed with focal epilepsy, 19 (15.8%) with generalized epilepsy, and 16 (15.8%) with combined epilepsy, while 8 patients (7.9%) had an unknown epilepsy type. The cohort included rare epilepsy syndromes: 8 patients with Lennox-Gastaut syndrome, 3 with Dravet syndrome, and 1 with Rasmussen syndrome. Patients had a history of various antiseizure medications (ASMs) (6.42 ± 3.15), and on average, were being treated with more than two (2.57 ± 1.16) drugs at the time of BRV deployment. RESULTS: Retention rates were high, with 80.6% of patients adhering to treatment at 3 months, 66.7% at 6 months, and 45.2% at 12 months. In 29 patients (30.1%), BRV was added in an overnight switch from levetiracetam (LEV), resulting in a reduction of behavioral adverse effects (AEs) in 5 patients (17.2%). The response rate was 25.8% at 3 months, 16.1% at 6 months, and 17.2% at 12 months, with no responders in the epileptic encephalopathy group. Therapy tolerance was notable, with 70 patients (75.3%) reporting no AEs. Transient AEs occurred in 10 patients (10.7%), and in 13 cases (14.0%), the AEs warranted dose adjustment or discontinuation of BRV. CONCLUSION: Approximately one-fifth of pediatric patients with drug-resistant epilepsy responded to BRV, with the best response observed in patients with focal seizures. However, the impact on patients with epileptic encephalopathy was limited.
Keywords: dítě; antikonvulziva; Adolescent; Anticonvulsants; Treatment Outcome; Retrospective Studies; Pediatric epilepsy; předškolní dítě; Pyrrolidinones; lidé; Response rate; Female; Brivaracetam; Overnight switch; výsledek terapie; pyrrolidinony; Epilepsy; Male; ženské pohlaví; Child; Humans; mužské pohlaví; epilepsie; Side effects; Retention rate; Child, Preschool; mladiství; retrospektivní studie